A study of some Biological Aspects of Procellio scaber(Isopoda : porcellionidae) Latrellile 1804In Al-jadriyia region /Baghdad-Iraq (Baghdad Science Journal, 2025)
A study of some biological aspects of the crustacean Isopod procellio scaber was carried out for the period April 2003 to march 2004 . The study consisted reproductive and morphological characteristies such as size , weight and length of the body . The result showed that the highest population density of P. scaber was 1120 individual/m2 in September 2003 and less density 403 ind/m2 in February 2004. The density was generally high in Spring and Autumn, low in Summer and Winter months.An increase of the sexual ratio appear in the females number compared to males number (p < 0.05) during most of year. Present study showed non significant increase in the length and dry weight for females compared to males in most of year months. There were two seasons for reproduction, first starts in February to the ends of August, the second season starts in September,to the end in January. A number of Juveniles recorded during most time of year. While the percentage decreased during the Winter months and nearly disappeared during December. The large size individuals dominated during the Spring season which may be due to their rapid growth. The results showed that the moult individuals in different sizes class present for most year months, in large numbers small sizes class include due to their rapid growth. Life cycle data showed four biological stages: eggs, Manca, Juvenile and Mature stages. The female put between (2-70) eggs per each breed. There is one or tow breed for female in year.